Characterisation of surface martensite-austenite transformation during finish turning of an AISI S15500 stainless steel. (1st January 2014) - Mondelin, Alexandre; Rech, Joël; Feulvarch, Eric; Coret, Michel
During machining, extreme temperature conditions appear in the cutting zone (from 700 to 1, 000°C with heating rates around 10 6 °C/s). Consequently, the metallurgical models used to simulate the impact of the manufacturing process must be adapted to this fast thermal kinetics. Stress-free dilatometry tests have been performed to determine the austenisation kinetics of an AISI S15500 martensitic stainless steel and to identify a phenomenological model. Experimental heating rates vary from 6 °C/s to 11, 000 °C/s. The metallurgical model calibrated for high heating rates, has been applied to a typical machining thermal cycle. It has been shown that martensite→austenite transformation does not have the time to significantly occur during the finish turning of AISI S15500 under standard cutting conditions. This result has been confirmed using retained austenite measurements in the machined surface layer.